2020
DOI: 10.1080/1828051x.2020.1729667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tannins and monensin on feeding behaviour, feed intake, digestive parameters and microbial efficiency of nellore cows

Abstract: 2020) Effect of tannins and monensin on feeding behaviour, feed intake, digestive parameters and microbial efficiency of nellore cowsABSTRACT This study aimed to evaluate the associative effect of monensin and tannins on intake, feeding behaviour, digestibility, rumen kinetics, microbial protein synthesis and nitrogen balance. In a 2 Â 4 factorial arrangement, 8 rumen cannulated Nellore cows were distributed in 2 contemporary 4 Â 4 Latin squares and received 8 diets that differed in the level of tannins (0.00,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Considering that the HS used in the present trial mainly contained HT, our results are in agreement with the findings of Costa et al [52] who showed higher diet palatability when hydrolysable tannin extract from chestnut instead of condensed tannin extract from mimosa was incorporated into oil-supplemented diets fed to sheep. However, tannins also directly inhibit cellulolytic microorganisms and fibrolytic enzymatic activity and increase rumen physical filling, because of the formation of complexes with lignocellulose that depress fiber digestion [53]. These phenomena could be the reason of the observed reduction of hay intake and, consequently, of total DMI, in our trial.…”
Section: Dry Matter Intake Milk Yield and Milk Main Constituentsmentioning
confidence: 71%
“…Considering that the HS used in the present trial mainly contained HT, our results are in agreement with the findings of Costa et al [52] who showed higher diet palatability when hydrolysable tannin extract from chestnut instead of condensed tannin extract from mimosa was incorporated into oil-supplemented diets fed to sheep. However, tannins also directly inhibit cellulolytic microorganisms and fibrolytic enzymatic activity and increase rumen physical filling, because of the formation of complexes with lignocellulose that depress fiber digestion [53]. These phenomena could be the reason of the observed reduction of hay intake and, consequently, of total DMI, in our trial.…”
Section: Dry Matter Intake Milk Yield and Milk Main Constituentsmentioning
confidence: 71%
“…The trend noticed in Table 3 revealed high fractional rate of gas production in Dioclea reflexa seed, and this could translate to availability of adequate nitrogen and high dry matter intake of ruminants for an improved performance. The highest OMD, SCFA, ME and IVDMD obtained in Dioclea reflexa compared to other test seeds implies that the microbes activities may be enhanced in the rumen and increase nutrients uptake (Chumpawadee et al 2007;Ramos et al 2020). The volume of gas produced is a function of relatively high protein quality and tolerable levels of anti-nutrients of the D. reflexa (Figs.…”
Section: Discussionmentioning
confidence: 93%
“…n = 3 Omotoso et al Bull Natl Res Cent (2020) 44:175 nutritional value of leguminous plants and hinder nutrient absorption (Table 2). Tannins are polyphenolic compounds capable of forming stable complexes with proteins, minerals and vitamins A and B 12 , which results in deterioration of the digestibility and availability of nutrients (Ramos et al 2020). Their negative impact is reflected not only in deterioration of protein digestibility through complexation thereof, but also in blocking the activity of proteolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total daily urinary volume was estimated, according to Tseu et al [ 22 ]. The nitrogen balance was obtained by the difference between the total nitrogen ingested and the total nitrogen excreted in feces and urine.…”
Section: Methodsmentioning
confidence: 99%